(untitled) (LEARNing Landscapes, 2021)
Societal views of Deaf people typically stem from a medical or deficit perspective, which then informs educational practices. In contrast, educational settings that embrace a cultural perspective provide visual language and strategies that can benefit all students. This article will address three common myths about American Sign Language (ASL) and Deaf people and share research-supported pedagogical practices and recommendations on how to be an ally on behalf of Deaf people.